Genetic variants help define the role of the MC4R C-terminus in signaling and cell surface stability - Moore, Bryn S.; Mirshahi, Tooraj (Scientific reports, 2018)
Screening 92,445 subjects in the Geisinger-Regeneron DiscovEHR cohort, we identified 5 patients heterozygous for nonsense mutations causing early terminations at Glu307 or Leu328 on the C-terminus of melanocortin 4 receptor (MC4R). Two Q307Ter carriers are severely obese (BMI > 40), while one is overweight (BMI > 25). One L328Ter carrier is overweight and the other is lean. Pedigree analysis for two Q307Ter carriers shows segregation of the variant with higher BMI. Functionally, MC4R(Q307Ter) eliminated receptor surface expression and signaling, while MC4R(L328Ter) functioned like the wild-type receptor. MC4R(Q307Ter) is therefore a loss of function (LOF) variant and the region between the two truncation sites identified in our patients is critical to MC4R function. Truncating MC4R at various C-terminal positions between these two variant sites, we find that cysteine318 sits at a critical junction for receptor trafficking and function. We show that MC4R is lipid modified at cysteine318 and cysteine319. Therefore, truncation early in the MC4R C-terminus results in haploinsufficiency in humans while truncation after the first lipid-modification site is well tolerated. MC4R haploinsufficiency clearly segregates with higher BMI; however, severe obesity is not fully penetrant even in MC4R LOF carriers, suggesting critical roles for environmental and lifestyle factors in MC4R monogenic obesity.